Case Report: Recurrent Left Posterior Fascicular Ventricular Tachycardia in a Newborn - Zhao, Lu; Wu, Lin; Zhao, Qu-ming; Liang, Xue-cun (Frontiers in Pediatrics, 2021)
Left posterior fascicular ventricular tachycardia is very rare in neonate. The QRS complex during the tachycardia is very similar to that in sinus rhythm in infants, so it is easily misdiagnosed as SVT. Although LPVT is typically considered as a benign ventricular tachycardia and tolerated well in infants, incessant VT can lead to reversible tachycardia cardiomyopathy and heart failure. We reported a 17-day-old newborn who presented with narrow QRS complex tachycardia. Intravenous adenosine and electrical cardioversion were not effective for persistent tachycardia. Amiodarone infusion was administrated to terminate the tachycardia. Oral amiodarone and propranolol were taken as maintain therapy to prevent cardiac arrhythmias. When the patient was nine-month old, the antiarrhythmic drugs were off free and the patient has no record of recurrence of tachycardia since then. LPVT is difficult to be diagnosed in infancy. The ORS morphology of right bundle branch block and superior axis morphology are the characteristics of LPVT. If adenosine is not effective in reverting presumed SVT, the diagnosis of LPVT should be considered. With proper diagnosis and treatment, LPVT could be regressed over time.